HOW TEACHERS HANDLE CLASSROOM MANAGEMENT PROBLEMS - Ismoilova Dillobarxon Kamoliddin qizi; Kosimova Mukammal Umaraliyevna (Ta’lim innovatsiyasi va integratsiyasi, 2023)
Annotation: This article defines classroom management and lists actual issues that teachers face in this area. It also attempts to clarify that keeping order and enforcing rules are only two aspects of effective classroom management. This has to do with getting the learner to focus and maintaining it, keeping the student's flexibility, and establishing sufficiency.